2018
DOI: 10.1016/j.bpj.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The Margination of Particles in Areas of Constricted Blood Flow

Abstract: Stroke is a leading cause of death globally and is caused by stenoses, abnormal narrowings of blood vessels. Recently, there has been an increased interest in shear-activated particle clusters for the treatment of stenosis, but there is a lack of literature investigating the impact of different stenosis geometries on particle margination. Margination refers to the movement of particles toward the blood vessel wall and is desirable for drug delivery. The current study investigated ten different geometries and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 66 publications
1
18
1
Order By: Relevance
“…Platelets exhibit a phenomenon called platelet margination or lateral drift, in which the concentration of platelets is highest near the vessel wall (Namdee et al, 2013; Vahidkhahb et al, 2014). This seems to be the result of an interaction with RBC (Vahidkhah et al, 2013; Carboni, 2017). When a platelet comes across a RBC, either a crossing or a turning interaction occurs.…”
Section: Dynamic Interactionsmentioning
confidence: 98%
“…Platelets exhibit a phenomenon called platelet margination or lateral drift, in which the concentration of platelets is highest near the vessel wall (Namdee et al, 2013; Vahidkhahb et al, 2014). This seems to be the result of an interaction with RBC (Vahidkhah et al, 2013; Carboni, 2017). When a platelet comes across a RBC, either a crossing or a turning interaction occurs.…”
Section: Dynamic Interactionsmentioning
confidence: 98%
“…Therefore, based on these data, we did not expect significant margination effect in this study due to the low shear rates observed in KD aneurysms (100 s −1 ) from our hemodynamic simulations and the typical length of coronary arteries. In addition, geometry changes such as expansions or constrictions have been reported to significantly effect particle margination [60]. For these reasons, here we considered the full 3D fluid domain in our calculations of platelet activation and platelet accumulation.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…These products are used as biomarkers, indicating the presence of certain diseases in an individual. [1][2][3] However, blood cells sometimes interfere in the biochemical readout of the results. Hence, plasma cell separation is essential in disease diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…These systems must be portable, but also accurate, reliable, rugged and well suited to the medical and social contexts of the developing world. [1,4] The microfluidic plasma-separation methods have the capability of direct connection to miniaturized sensors. Thus, they can create miniaturized POC or can be embedded in small machines for screening a large number of people in a short period (i.e.…”
Section: Introductionmentioning
confidence: 99%